Kontribusi Lingkungan Belajar Dan Fasilitas Belajar Terhadap Hasil Belajar Akuntansi Perusahaan Jasa Pada Mahasiswa Program Studi Pendidikan Akuntansi Universitas Muhammadiyah Surakarta Angkatan 2015 - Wulandari, Ika Noviati, Dr. Wafrotur Rohmah, M.M (2016)
environment on learning outcomes. 2) To determine the contribution of learning facility on learning outcomes. 3) To determine the contribution of the learning environment and learning facilities for learning outcomes. This study includes quantitative descriptive research type with a conclusion through statistical.Populationmethods in this study were all students of the faculty of teacher training and education science courses accounting education University of Muhammadiyah Surakarta force 2015. Samples are taken as 139 students with simple random sampling. The necessary data obtained through questionnaires and documentation. Questionnaire previously tested and tested for validity and reliability were tested. Data analysis technique used is multiple linear regression analysis, t-test, f-test, and the relative contribution and effective. The results of the regression analysis obtained regression equation: Y = 11,702 + 0,281 X1 + 0,472 X2. The equation shows that the learning outcomes are influenced by the learning environment and learning facilities. The conclusions drawn are: 1) the learning environment to the learning outcomes are acceptable. This is based on multiple linear regression analysis (ttest) note that t > t table, 3,429 > 1,960 and significant value < 0,05, namely 0,001 with the relative contribution of 28,6% and 10,6% effective contribution. 2) Learning facilities to the learning outcomes are acceptable this is based on multiple linear regression analysis (ttest) note that t > t table, namely 5,754 > 1,960 andsignificant value< 0,05, namely 0,000 with the relative contribution of 71,4% and 26,6% effecrive contribution. 3) The learning environment and learning facilities to the learning outcomes are acceptable. This is based on multiple linear regression analysis of variance (Ftest) is known that Fcount >Ftable is 25,390 > 3,000 andsignificant value< 0,05, namely 0,000. The coeficient of determination (R2) of 0,372 indicates that the influence of the learning environment and learning facilities for learning outcomes was 37,2%, while the rest influenced by other variables, that is equal 62,8%.